PENGARUH PROCEDURAL FAIRNESS, DISTRIBUTIVE FAIRNESS, INTERACTIONAL FAIRNESS, TERHADAP KEPUASAN PELANGGAN - Jatmiko, M. Roby (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2012)
This study examined three independent variables, ie Procedural Fairness, Distributive Fairness, and Interactional Fairness can affect customer satisfaction. The purpose of this study was to determine the effect of the three independent variables on customer satisfaction. This research was conducted with a questionnaire to 100 PLN customer obtained by using purposive sampling techniques. The data that have met the test of validity, reliability, and test the assumptions of classical. These results indicate that all the independent variables tested are positive and significant impact on customerÂ  satisfaction through the F test and t test, whereas the number Adjusted R Square of 0.236 indicates 23,60%of the variation in people satisfaction which can be explained by the third independent variable, where the remaining 76.40% is explained by other factors outside of the study. Â  Keywords: Procedural Fairness, Distributive Fairness, Interactional Fairness, customer satisfaction